Effect of citric acid and vermi-wash on growth and metal accumulation of Sorghum bicolor cultivated in lead and nickel contaminated soil. (March 2020) - Rathika, R.; Khalifa, Ashraf.Y.Z.; Srinivasan, P.; Praburaman, L.; Kamala-Kannan, S.; Selvankumar, T.; Kim, Woong; Govarthanan, M.
Abstract: The aim of the present study is to assess the influence of vermi-wash (VW) and citric acid (CA) on Sorghum bicolor growth and phytoaccumulation of lead (Pb) and nickel (Ni) contaminated soil. The biomass of the S. bicolor has been enhanced by the addition of VW (24 and 26%) and CA (11 and 9%) in Pb and Ni contaminated soil, respectively. The VW treatment showed enhanced shoot and root lengths and chlorophyll concentrations compared to CA. The shoot anatomic structure showed an accumulation of Pb and Ni were positively impacted by the amendment of VW and CA. In addition, VW treatment showed enhanced antioxidant enzymes activity (140, 125 and 152 U/mg of CAT, SOD and POD). Further, the plants grown in Pb contaminated soil treated with VW showed enhanced Rubisco activity of 1.49 U/ml, whereas, CA treatment showed 1.23 U/ml of Rubisco. It has been observed that the VW showed as a potential chelator as well as plant beneficial formulation for the enhanced phyto-remediation of Pb and Ni. Highlights: The biomass of the S. bicolor has been enhanced by the addition of VW (24, and 26%) and CA (11, and 9%) in Pb and Ni contaminated soil respectively. The shoot anatomic structure showed an accumulation of Pb and Ni were positively impacted by the amendment of VW and CA. VW showed enhanced antioxidant enzymes activity (140, 125 and 152 u/mg of CAT, SOD and POD). Pb contaminated soil treated with VW showed enhanced Rubisco activity of 1.49 U/ml, whereas, CA treatment showed 1.23 u/ml of Rubisco.